PENGARUH PERCEIVED VALUE TERHADAP KEPUASAN PELANGGAN PADA JASA TATA RIAS PENGANTIN TUNJUNG SETO DENGAN KUALITAS PELAYANAN SEBAGAI VARIABEL MEDIASI - Maharany Jana Siry (Universitas Slamet Riyadi, 2015)
The aim of this study were: 1) to analyze the effect of perceived value on the quality of service on bridal makeup services Tunjung Seto. 2) Analyze the effect of perceived value on customer satisfaction in service bridal Tunjung Seto. 3) Analyze the impact of service quality on customer satisfaction in service bridal Tunjung Seto. 4) Analyze the effect of perceived value on customer satisfaction in service bridal Tunjung Seto mediated quality of service. In conclusion: 1) Perceived value significantly influence the quality of service on bridal makeup services Tunjung Seto. 2) Perceived value significantly influence customer satisfaction in service bridal Tunjung Seto. 3) Quality of care significantly influence customer satisfaction in service bridal Tunjung Seto. 4) Satisfaction influence service quality perceived value to customer satisfaction in service bridal Tunjung Seto, is evident from the results of the path analysis, in which the indirect effect coefficient (0,848) > direct influence coefficient (0,599). Keywords: Tunjung Seto, Perceived Value, Quality of Service, Customer Satisfaction